Conversion of Low-Flow Priapism to High-Flow State Using T-Shunt with Tunneling - Neil A. Mistry; Nicholas N. Tadros; Jason C. Hedges (Case Reports in Urology)
Introduction. The three types of priapism are stuttering, arterial (high-flow, nonischemic), and venoocclusive (low-flow, ischemic). These are usually distinct entities and rarely occur in the same patient. T-shunts and other distal shunts are frequently combined with tunneling, but a seldom recognized potential complication is conversion to a high-flow state. Case Presentation. We describe 2 cases of men who presented with low-flow priapism episodes that were treated using T-shunts with tunneling that resulted with both men having recurrent erections shortly after surgery that were found to be consistent with high-flow states. Case 1 was a 33-year-old male with sickle cell anemia and case 2 was a 24-year-old male with idiopathic thrombocytopenic purpura. In both cases the men were observed over several weeks and both men returned to normal erectile function. Conclusions. Historically, proximal shunts were performed only in cases when distal shunts failed and carry a higher risk of serious complications. T-shunts and other distal shunts combined with tunneling are being used more frequently in place of proximal shunts. These cases illustrate how postoperative erections after T-shunts with tunneling can signify a conversion from low-flow to high-flow states and could potentially be misdiagnosed as an operative failure.